2012
DOI: 10.4103/0976-7800.98815
|View full text |Cite
|
Sign up to set email alerts
|

A study of predictors of anxiety and depression among stroke patient-caregivers

Abstract: Context:Caregivers play an important role in supporting people with illness either acute or chronic. It is important to explore caregiver's emotional turmoil as it helps in exploring their burden which can have impact on the patient's illness and functioning apart from their own.Aims:The current study aimed at assessing the predictors of anxiety and depression among caregivers of patients with stroke.Settings and Design:Seventy-five consecutive patient-caregiver dyads were recruited in the study.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
4
30
2
2
Order By: Relevance
“…This appeared to be significant in the chronic stage of stroke although, consistently with earlier studies, it was also significantly associated with the burden in the post-acute phase [22,41]. Elevated anxiety within the first months after stroke has been explained in the literature by caregivers' uncertainty about the future, for both the stroke survivors and for themselves, and by specific difficulties in that period [46,47]. Other factors however, such as increased mobilisation, the necessity to keep busy with caregiving tasks without having time for reflection about all the uncertainties and the expectation of further recovery of the patient, can all moderate the anxious feelings of the carer at that time.…”
Section: Discussionmentioning
confidence: 57%
“…This appeared to be significant in the chronic stage of stroke although, consistently with earlier studies, it was also significantly associated with the burden in the post-acute phase [22,41]. Elevated anxiety within the first months after stroke has been explained in the literature by caregivers' uncertainty about the future, for both the stroke survivors and for themselves, and by specific difficulties in that period [46,47]. Other factors however, such as increased mobilisation, the necessity to keep busy with caregiving tasks without having time for reflection about all the uncertainties and the expectation of further recovery of the patient, can all moderate the anxious feelings of the carer at that time.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have shown that QOL, anxiety, depression and burden in stroke caregivers are interrelated. Balhara, Verma, Sharma, and Mathur () found that anxiety decreases caregivers’ QOL and increases their burden (Denno et al., ). Depression, which was found to be three times higher in stroke caregivers than in the general population (Cecil et al., ), decreases caregivers’ social QOL and it has even been associated with the deterioration of stroke survivors’ physical and cognitive functions (McCarthy & Lyons, ; McCarthy, Lyons, & Powers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, caregivers may experience poor physical health (Carretero, Garcés, Ródenas, & Sanjosé, 2009;Legg, Weir, Langhorne, Smith, & Stott, 2013) and reduced energy (Parag et al, 2008). Given the range of emotional and physical consequences faced by caregivers, typically referred to as caregiver burden (Rigby, Gubitz, & Phillips, 2009), it is unsurprising there is a higher prevalence of mental health difficulties such as depression and anxiety experienced by caregivers of stroke survivors than the general population (Balhara, Verma, Sharma, & Mathur, 2012;VisserMeily, Post, van de Port, van Heugten, & Bos, 2008). Indeed, 50% of caregivers of stroke survivors experience elevated symptoms of depression (Visser-Meily et al, 2008) and anxiety (Greenwood & Mackenzie, 2010a).…”
Section: Introductionmentioning
confidence: 99%